Efficient Natural Resources Management of Tahakapal Cluster Villages using Geospatial Technologies - Khalkho, D.; Patil, S. K.; Patel, S.; Pali, G. P. (International Journal of Bio-resource and Stress Management, 2023)
False colour composite (FCC) of IRS-P6 LISS IV geocoded data was interpreted in conjunction with survey of India (SOI) toposheet on 1:50000 scale to extract information on existing land use/ land cover, slope, aspect and physiography for characterization and mapping of soils in the cluster village Tahakapal, Block-Tokapal, Dist.-Bastar (Chhattisgarh) under NAIP-3 project. The revenue maps of 1:4000 scale was digitized and converted to vector shape file with attributes of field details like owners name & caste and coverage area, perimeter etc. This revenue map was overlapped to the FCC of mosaic satellite data for retrieving the true land characterization of the project area. Five farming situations were characterized and mapped as per the local names of the agro climatic zone viz. Badi, Marhan, Tikra, Mal and Gabhar. The badi (10.7%) comprises of upland settlement, marhan (40.5%) is the upper upland, tikra (17%) is the lower upland, mal (16.1%) comprises the midland part and gabhar (15.7%) is the low lying situation. Marhan are un-bunded with steep sloped situation. Tikra is the un-bunded upland entisols with steep slope. Mal, the midland, is characterised as Inceptisol, Alfisol, bunded, flat lands and Gabhar, the lowland, comprises of bunded, Alfisol/ Vertisol supports crops like long duration paddy in Kharif followed by gram, linseed, pea in Rabi. Additional water resources in the shape of shallow dug well and farm ponds were constructed following the drainage line of the area. Site specific land use have been suggested and demonstrated with suitable soil and water conservation measures for sustainable land resource management.